2020
DOI: 10.1177/0885328220926655
|View full text |Cite
|
Sign up to set email alerts
|

Conjugating heparin, Arg–Glu–Asp–Val peptide, and anti-CD34 to the silanic Mg–Zn–Y–Nd alloy for better endothelialization

Abstract: Magnesium alloy is generally accepted as a potential cardiovascular stent material due to its good mechanical properties, biocompatibility, and biodegradability, and has become one of the research hotspots in this field. However, too fast degradation rate and delayed surface endothelialization have been the bottleneck of further application of magnesium alloy stent. In this study, we selected Mg–Zn–Y–Nd, a kind of biodegradable magnesium alloy for cardiovascular stent, and passivated its surface by al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Furthermore, HR tests revealed that LDH/PDA/Hep coating had a low HR (0.65%) in vitro, implying that heparinization was a promising strategy to enhance the hemocompatibility of samples. Li et al [ 242 ] conjugated the Hep molecule, the Arg–Glu–Asp–Val peptide (REDV, which is a tetrapeptide derived from fibronectin that can be specifically recognized by α 4 β 1 integrin on the surface of ECs [ 243 ]), and an anti-CD 34 antibody (CD 34 is a highly glycosylated type I transmembrane glycoprotein that interacts with anti-CD 34 antibodies and is an important way to promote EPC-targeted adhesion/capture [ 244 , 245 ]) on a silane-treated ZE21B alloy, for improving surface endothelialization. A blood compatibility test suggested that multi-functional coating effectively restrained platelet adhesion/activation and reduced the HR (<5%).…”
Section: Surface Modification Of Mg Alloy Stentsmentioning
confidence: 99%
“…Furthermore, HR tests revealed that LDH/PDA/Hep coating had a low HR (0.65%) in vitro, implying that heparinization was a promising strategy to enhance the hemocompatibility of samples. Li et al [ 242 ] conjugated the Hep molecule, the Arg–Glu–Asp–Val peptide (REDV, which is a tetrapeptide derived from fibronectin that can be specifically recognized by α 4 β 1 integrin on the surface of ECs [ 243 ]), and an anti-CD 34 antibody (CD 34 is a highly glycosylated type I transmembrane glycoprotein that interacts with anti-CD 34 antibodies and is an important way to promote EPC-targeted adhesion/capture [ 244 , 245 ]) on a silane-treated ZE21B alloy, for improving surface endothelialization. A blood compatibility test suggested that multi-functional coating effectively restrained platelet adhesion/activation and reduced the HR (<5%).…”
Section: Surface Modification Of Mg Alloy Stentsmentioning
confidence: 99%
“…Alloying with other elements and surface modification are the most commonly used methods to control the degradation rate [ 23 ]. After alloying with REEs, the Mg-Zn-Y-Nd alloy used in our study not only improved its anticorrosion resistance, but also maintained its good biocompatibility and clinical applicability, which has been demonstrated in various in vitro and in vivo studies [ 24 26 ]. In addition, there was a uniform coating on the surface of the material, the main components of which were MgF 2 and Mg (OH) 2 (Figures 3 and 4 ).…”
Section: Discussionmentioning
confidence: 58%
“…At the 4 h, 24 h, and 72 h after cultured using the extracts, the HUVECs were fixed with 4% paraformaldehyde (Sigma) at RT and stained with rhodamine and DAPI, and observed under a confocal laser scanning microscope (CLSM, Nikon C2 Plus, Tokyo, Japan) [ 49 ]. The viability and nitric oxide (NO) release of HUVECs were detected by a typical ELISA method and calculated according to the previous study [ 50 , 51 ].…”
Section: Methodsmentioning
confidence: 99%